2021
DOI: 10.1186/s13063-021-05885-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the peripherally acting μ-opioid receptor antagonist methylnaltrexone on acute pancreatitis severity: study protocol for a multicentre double-blind randomised placebo-controlled interventional trial, the PAMORA-AP trial

Abstract: Background Moderate to severe acute pancreatitis (AP) is associated with a high rate of complications and increased mortality, yet no targeted pharmacologic treatment currently exists. As pain is a dominant symptom in AP, patients are exposed to excess levels of both endo- and exogenous opioids, which may have harmful effects on the course of AP. This trial investigates the effects of the peripherally acting μ-opioid receptor antagonist (PAMORA) methylnaltrexone on disease severity and clinical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…RAPID-I has wide entry criteria, includes healthrelated quality of life and costs as outcomes, with follow-up of 3 months. The third is a Danish trial of the peripherally acting µ-opioid receptor antagonist methylnaltrexone, which counteracts inhibitory effects of opiates on gut function and immune responses, without affecting analgesia [266]. It is to be hoped these trials will be completed soon and that the international impetus for such trials will grow.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…RAPID-I has wide entry criteria, includes healthrelated quality of life and costs as outcomes, with follow-up of 3 months. The third is a Danish trial of the peripherally acting µ-opioid receptor antagonist methylnaltrexone, which counteracts inhibitory effects of opiates on gut function and immune responses, without affecting analgesia [266]. It is to be hoped these trials will be completed soon and that the international impetus for such trials will grow.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…As such, retrospective studies have shown that opioid treatment increased the risk of 30‐day mortality, invasive ventilation, vasopressor treatment, abdominal surgery, increased morphological severity of AP, and longer length of admission. 13 , 24 , 25 Furthermore, peripheral μ‐opioid receptor antagonists are currently being tested in patients with predicted severe and recurrent AP 7 , 26 due to their potential to counteract opioid‐induced alterations to the gastrointestinal and immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…5 There are many potentially harmful effects of opioids on the human gastrointestinal tract, which could influence the course and outcome of AP . [6][7][8] Opioids can cause intestinal dysmotility, ileus, and bacterial overgrowth as well as increased intestinal permeability, which in turn might increase the risk of bacterial translocation, infected pancreatic necrosis, and worsen the severity of AP. 9 Furthermore, opioid administration may contribute to immunosuppression, which may promote infections.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids also increase gut transit time which can cause bacterial overgrowth that can cause pain and bloating. Preclinical studies have shown that opioids can increase intestinal permeability, which is known to increase the translocation of bacteria and the risk of local and systemic infections, which might be promoted by opioid-induced immunosuppression [27]. It is customary to treat opioid induced intestinal dysmotility with laxatives although there is little evidence for r which specific laxative is most effective.…”
Section: Treating Pain In Acute Pancreatitismentioning
confidence: 99%
“…It is customary to treat opioid induced intestinal dysmotility with laxatives although there is little evidence for r which specific laxative is most effective. Recognizing that endogenous opioids, released in response to pain and visceral injury, also contribute to dysmotility means that laxatives might be required even when opioids are not prescribed [27]. There appears to be a role for peripherally acting μ-opioid receptor antagonists that have been shown to be effective in treating postoperative ileus and chronic constipation that share common mechanisms to that seen in opioid induced intestinal dysmotility [28].…”
Section: Treating Pain In Acute Pancreatitismentioning
confidence: 99%